Progressive encephalopathy in a Crohn's disease patient on long-term total parenteral nutrition: possible relationship to selenium deficiency. Issue 821 (March 1994) - Kawakubo, K.; Iida, M.; Matsumoto, T.; Mochizuki, Y.; Doi, K.; Aoyagi, K.; Fujishima, M.
Abstract : The case of a patient with Crohn's disease complicated by progressive and irreversible encephalopathy, who had been on long-term total parenteral nutrition due to short bowel syndrome, is described. He initially experienced a disturbance of his vision, which was followed by various neurological symptoms during the next 3 years. These symptoms rapidly progressed until he finally developed consciousness disturbance. He also manifested erythrocytic macrocytosis, a low serum level of tri-iodothyronine and a high level of thyroxine. His blood levels of various trace minerals and vitamins were normal, except for selenium, which showed extremely low values. In addition, impaired plasma glutathione peroxidase activity was confirmed. After intravenous supplementation of selenium, macrocytosis, tri-iodothyronine and thyroxine values, and glutathione peroxidase activity all became normalized, yet he improved little neurologically. Our case suggests that long-term selenium deficiency may cause progressive and irreversible encephalopathy, and that careful monitoring of this mineral is necessary when an excessive period of total parenteral nutrition is being considered in the clinical setting.